Ultrasound Guided Pericardial Effusion Training Model for Neonates - Monalisa Patel (International Journal of Neonatology, 2024)
This methods article presents a neonatal pericardial effusion training model using ultrasound. It details materials, construction, and training objectives to support procedural competence.
Keywords: Pericardiocentesis